The high-performance light transmitting concrete and experimental analysis of using polymethylmethacrylate optical fibers in it. (June 2021) - Navabi, Danial; Javidruzi, Mahyar; Hafezi, Mohammad Reza; Mosavi, Amir
Abstract: The purpose of the current study is to investigate the optical and physical properties of high-performance light transmitting concrete which was prepared by Portland cement, polymethylmethacrylate (PMMA) optical fibers, silica fume, fine aggregate, polycarboxylate superplasticizer, silica powder, and water in a given proportion. Many samples of light transmitting concrete with 3, 5, 7, 10, & 15% volumetric PMMA optical fibers in it were produced. The laboratory tests were determined in order to specify the optimum fraction of optical fibers in samples in terms of performance, and evaluation of light transmitting properties of concrete based on single high-performance concrete mixing design depending on optical fibers quantity. As the findings revealed, the compressive strength decreased with an increasing volume fraction of optical fiber in the light transmitting concrete samples. Light transmitting performance of specimens was tested by the designed lightbox and optical power method (spectrometer test). Optical power increased nonlinearly with an increasing number of optical fibers; however, it does not transmit infrared waves as well as visible waves. Considering the light transmittance of light transmitting concrete samples, compressive strength, and the amount of used optical fibers in them, the light transmitting concrete sample that contains 10% of the volumetric optical fibers in it, can be optimum in terms of cost and performance. Highlights: The concrete samples that contain 10% optical fiber can be optimum in terms of cost and performance. Compressive strength of light transmitting concrete decreases with an increasing volume fraction of PMMA optical fibers. Optical power of light transmitting concrete increases nonlinearly with an increasing number of optical fibers. Light transmitting concrete does not transmit infrared waves as well as visible waves.